Analisis Kesulitan Belajar Bahasa Arab Siswa Kelas IX Di SMP IT Insan Cendikia Makassar - Muhammad Farid; Abdul Wahab; Ansar Ansar (Universitas Muslim Indonesia, 2022)
This study discusses difficulties in learning Arabic and aims to determine the forms of difficulties in learning Arabic for grade IX students, and efforts to overcome learning difficulties in Arabic subjects at SMPIT Insan Cendekia Makassar. This type of research is qualitative research. The subjects of this study were teachers and students. The determination of the research subjects was carried out using a purposive sampling technique, totaling 10 informants. Methods of data collection using interviews, observation, and documentation. The results showed that there were forms of difficulty in learning Arabic for grade IX students at SMP IT Insan Cendekia Makassar, namely internal and external factors, internal factors consisted of cognitive, affective, and psychomotor. the student, then the external factors consist of the family environment and the school environment, efforts to overcome the difficulties of the Arabic language made by teachers and students by applying the vocabulary method and using textbooks or dictionaries.